Pengaruh Keadilan Organisasi dalam Penilaian Kinerja terhadap Kepuasan Penilaian dan Kinerja Karyawan - Masrukin Masrukin; Musa Hubeis; Hari Wijayanto (Universitas Airlangga, 2018)
Since 2012, management of PTPN V Pekanbaru implemented a new system of performance appraisal, named Competency-Based Performance Management (CBPM) for replaced the earlier system. The difference between CBPM and the earlier system is CBPM use a set of measured performance indicator, while in the old system, performance appraisal done by graphic rating scale method. One of performance appraisal effectiveness indicator is organizational justice on performance appraisal. The purpose of this study is to analyze organizational justice in performance appraisal and their influence on satisfaction toward performance appraisal and employee’s performance. Data collected from 196 respondents from managerial employee by a set of online questionnaire with purposive sampling’s technique. Descriptive analysis carried out by mean value’s analysis and range’s criteria analysis. Hypothesis testing has done by Structural Equation Modelling-Partial Least Square (SEM-PLS) analysis. The descriptive analysis shows that organizational justice in the performance appraisal had run well and the employees had satisfied toward the performance appraisal. SEM-PLS analysis shows that organizational justice in performance appraisal effect to satisfaction of performance appraisal and employee’s performance significantly. Satisfaction toward performance appraisal does not play a role in mediating the influence of justice in the performance appraisal to employee performance